IMPLEMENTASI MANAJEMEN KEARSIPAN DALAM MENINGKATKAN ADMINISTRASI SEKOLAH DI MTS AL-YASINI - Ulul Masrifah; M.Syaikhudin (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
A well-organized school administration cannot be separated from systematic and orderly records management. Records play a crucial role in supporting administrative activities, including services, reporting, and accreditation processes. However, in practice, many educational institutions still face challenges in managing their records, making research on the implementation of records management relevant to conduct. This study aims to examine the implementation of records management in improving school administration at MTs Al-Yasini Pasuruan and to identify the supporting and inhibiting factors in its application. This research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. The research subjects include the principal, the head of administration, administrative staff, and teacher representatives. The findings show that records management at MTs Al-Yasini follows the five stages of the records cycle proposed by Read and Ginn, namely creation, handling, use, storage, and disposition of records. This implementation contributes to improving the quality of school administration, as evidenced by faster services, easier document retrieval, and a more orderly documentation system. Supporting factors include leadership commitment, discipline among administrative staff, availability of physical facilities, and the use of digital technology. Meanwhile, inhibiting factors consist of the absence of professional archivists, the lack of written SOPs, limited storage space, and insufficient staff training. Therefore, although the implementation of records management has been running well and has provided positive contributions, strengthening regulations, enhancing human resource capacity, and developing a more integrated digital system are still required to meet national archival standards